2014
DOI: 10.1111/imj.12468
|View full text |Cite
|
Sign up to set email alerts
|

Eltrombopag for resistant immune thrombocytopenia secondary to chronic lymphocytic leukaemia

Abstract: Autoimmune manifestations are a common occurrence with chronic lymphocytic leukaemia (CLL). We describe a case of CLL-associated immune thrombocytopenia (ITP) that had a loss of response to standard treatment for ITP. The thrombopoeitin receptor agonist, eltrombopag, was successfully used preoperatively to increase the platelet count to a safer level, in this instance to facilitate laparoscopic splenectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…49,50 These agents have also shown durable responses in patients with refractory CLL-associated ITP, and may be considered in patients with minimal CLL disease burden and unremitting severe thrombocytopenia. 51,52 Jain et al 53 demonstrated in their enrolling phase II trial of eltrombopag that at varying doses, eltrombopag produced an overall response in 55% of all patients with thrombocytopenia, either due to CLL-associated ITP or CLL marrow infiltration. Overall, both groups of patients had a 45% complete response (CR) or 9% major response (MR).…”
Section: Immune Thrombocytopeniamentioning
confidence: 99%
“…49,50 These agents have also shown durable responses in patients with refractory CLL-associated ITP, and may be considered in patients with minimal CLL disease burden and unremitting severe thrombocytopenia. 51,52 Jain et al 53 demonstrated in their enrolling phase II trial of eltrombopag that at varying doses, eltrombopag produced an overall response in 55% of all patients with thrombocytopenia, either due to CLL-associated ITP or CLL marrow infiltration. Overall, both groups of patients had a 45% complete response (CR) or 9% major response (MR).…”
Section: Immune Thrombocytopeniamentioning
confidence: 99%
“…Also, eltrombopag is currently approved by the US Food and Drug Administration and the European Medicines Agency for the treatment of thrombocytopenia secondary to aplastic anaemia (Olnes et al, 2012) and thrombocytopenia secondary to hepatitis C infection (McHutchison et al, 2007;Afdhal et al, 2012). Eltrombopag has also been successfully used in a very small number of patients with immune thrombocytopenia secondary to chronic lymphatic leukaemia (Koehrer et al, 2010;Sinisalo et al, 2011;Gudbrandsdottir et al, 2012;Jolliffe & Romeril, 2014;Chang & Shih, 2015), systemic lupus erythematosus (SLE: Chang & Shih, 2015;Gonzalez-Nieto et al, 2011;Alkaabi et al, 2012;Scheinberg et al, 2014;Magnano et al, 2014;Maroun et al, 2015), Evans syndrome (Gonzalez-Nieto et al, 2011;Alkaabi et al, 2012;Ruiz-Arguelles et al, 2013;Magnano et al, 2014;Scheinberg et al, 2014;Chang & Shih, 2015;Maroun et al, 2015), human immunodeficiency virus (Quach et al, 2012;Aslam et al, 2014;Chang & Shih, 2015;Kowalczyk et al, 2015) and coeliac disease (Chang & Shih, 2015) who had a loss of response to standard treatment for ITP. The communication of such cases is essential to support the potential utility of eltrombopag as salvage therapy in the treatment of secondary immune thrombocytopenia.…”
mentioning
confidence: 99%
“…Data are also reported about the use of TPO‐RAs for the treatment of thrombocytopenia related to hematologic, autoimmune, and infectious diseases, or to chemotherapy . In particular, the use of eltrombopag in chronic lymphocytic leukemia (CLL) associated ITP was described by different authors : in two cases, a CR was obtained and one patient could stop the drug ; in one case, eltrombopag was successfully used preoperatively to increase the platelet count to allow laparoscopic splenectomy ; in one other case, eltrombopag increased platelet count to normal range 13 days after treatment start in a patient who presented recurrent ITP associated to pulmonary hemorrhage . Al‐Nawakil et al reported the use of romiplostim in four ITP patients during the diagnostic phase or after diagnosis of lymphomas: 3/4 patients obtained a response.…”
Section: Discussionmentioning
confidence: 99%